Current and future technical, economic and environmental feasibility of maize and wheat residues supply for biomass energy application: Illustrated for South Africa. (September 2016) - Batidzirai, B.; Valk, M.; Wicke, B.; Junginger, M.; Daioglou, V.; Euler, W.; Faaij, A.P.C.
Abstract: This study assessed the feasibility of mobilising maize and wheat residues for large-scale bioenergy applications in South Africa by establishing sustainable residue removal rates and cost of supply based on different production regions. A key objective was to refine the methodology for estimating crop residue harvesting for bioenergy use, while maintaining soil productivity and avoiding displacement of competing residue uses. At current conditions, the sustainable bioenergy potential from maize and wheat residues was estimated to be about 104 PJ. There is potential to increase the amount of crop residues to 238 PJ through measures such as no till cultivation and adopting improved cropping systems. These estimates were based on minimum residues requirements of 2 t ha −1 for soil erosion control and additional residue amounts to maintain 2% SOC level. At the farm gate, crop residues cost between 0.9 and 1.7 GJ −1 . About 96% of these residues are available below 1.5 GJ −1 . In the improved scenario, up to 85% of the biomass is below 1.3 GJ −1 . For biomass deliveries at the conversion plant, about 36% is below 5 GJ −1 while in the optimised scenario, about 87% is delivered below 5 GJ −1 . Co-firing residues with coal results in lower cost of electricity compared to other renewables and significant GHG (CO2 eq) emissions reduction (up to 0.72 tons MWh −1 ). Establishing sustainable crop residue supply systems in South Africa could start by utilising the existing agricultural infrastructure to secure supply and develop a functional market. It would then be necessary to incentivise improvements across the value chain. Highlights: Sustainable bioenergy potential from crop residues estimated at 104–238 PJ. Key preconditions include switch to no till cultivation and improved farming systems. Sustainable residue removal require minimum 2 t ha −1 residues for erosion control. Sufficient residues also required to maintain SOC levels. At the farm gate, crop residues cost 0.9–1.7 GJ −1 .